Geometry symmetry-free and higher-order optical bound states in the continuum - Qingjia Zhou (Nature Portfolio, 2021)
Ensuring robustness of bound states in the continuum usually relies on precise control of geometrical symmetries, which are quite susceptible to fabrication imperfections. Here, the authors propose to exploit physical symmetries instead, as a way to achieve robust BICs in disordered systems.